Relationship Between Arterial Oxygen Saturation and Hematocrit, and Effect of Slow Deep Breathing on Oxygen Saturation in Himalayan High Altitude Populations - Nepal, Ojashwi; Pokharel, BR; Khanal, K; Mallik, SL; Kapoor, BK; Koju, R (Kathmandu University Medical Journal, 2013)
Background The oxygen saturation of haemoglobin is reduced in high altitude-living organisms. Increase in the hematocrit is responsible for rise in the hemoglobin concentration so that the oxygen carrying capacity in the hypobaric hypoxic subject is elevated. Objectives To compare two different high altitude populations, in order to study the relationship between arterial oxygen saturation and hematocrit. Methods lIn the cross-sectional study of two populations residing at altitude of 2800 m and 3760 m are compared for the difference in hematocrit. The oxygen carrying capacity of arterial haemoglobin (SaO2) is determined by pulse oximetry. The sample is drawn from the natives of two small villages, Thini at Jomsom (2800 m) and Jharkot (3760 m) in Mustang district of Nepal. The natives at 2800 m are termed as lower high altitude population and local residents at 3760 m are said to be higher altitude population in this study. The sample blood was drawn by venipuncture and packed cell volume was determined by Wintrobe’s method. Results The hematocrit obtained from 3760 m altitude population and the lower high altitude population at altitude of 2800 m differ significantly with the p value < 0.0001and the SaO2 in both the population fails to show any difference with p value > 0.05. Deep breathing exercise in these populations however increased SaO2 significantly. Conclusion The higher altitude natives have greater arterial oxygen saturation than lower altitude population which is due to rise in red cell concentration. The slow deep breathing raises oxygen saturation irrespective of altitude. Kathmandu University Medical Journal | VOL.10 | NO. 3 | ISSUE 39 | JUL- SEP 2012 | Page 30-34 DOI: http://dx.doi.org/10.3126/kumj.v10i3.8014